Exchange Rate "Fundamentals" versus Speculation : The Case of Lebanon. (IMF Working Papers; Working Paper ;, 1988)
The exchange rate for the Lebanese pound experienced a protracted period of depreciation from end-1982 to November 1987, followed by a marked appreciation over the following six months. This paper investigates the competing hypotheses that the exchange rate over these two periods was driven by a speculative bubble versus 'fundamental' economic variables. Reduced-form and time series models for the exchange rate are estimated and tested for nonstationarity. The results of these test suggest that the pound's volatility in recent years was consistent with an excessive growth in domestic versus foreign currency denominated liquidity rather than speculation.